Bacterial nano cellullose as non-active pharmaceutical ingredient production optimization, quality control development and prototype design - González, Exequiel Elías (2019)
Materials from bio-based resources have attracted immense research interest in recent years as a result of their very high potentials for fabricating several high-value products with low impact on the environment. Cellulose produced by some bacteria has received great attention. Bacterial Nano Cellulose (BNC) imparts attractive combinations of biophysicochemical characteristics and improved mechanical properties. The aims of this work was to develop growth media for increase BNC production, characterize a non-active pharmaceutical ingredient (NAPI), design an efficient quality control method by FTIR and SEM by compared that NAPI with commercial ones and present a first prototype of a pharmaceutical product. LB and KB media were modified and BNC obtained had better quality respect its crystallinity and/or polymerization degree than the BNC from commercial media. Different extraction processes were proposed, in no case microbiological material remnants has been found. Films for controlled drugs release prototype were made and its physical properties such as water solubility, moisture content, swelling property, UV barrier capacity were evaluated. BNC films present an additional advantage, having lower UV permeability than films with cellulose of vegetal origin, adding potentialities to a patch design that protects the tissue and the Active Pharmaceutical Ingredients.